Antipyretic, analgesic and anti-inflammatory activity of the methanol Mimosa himalayana extract - Hossain, Md.; Bashar, Md.; Ibrahim, Mohammed; Islam, Muhammad (International Journal of Medicine, 2017)
The aim of the study was to evaluate antipyretic, analgesic and anti-inflammatory activities of the methanol extract of Mimosa himalayana Gamble (Fabaceae) along with a preliminary phytochemical screening. The antipyretic and analgesic effects were tested in Swiss mice, while anti-inflammatory in egg albumin, taking paracetamol, diclofenac sodium and acetyl salicylic acid as standards, respectively. The results suggest that, the crude stem extract of M. himalayana revealed the presence of alkaloids, glycosides, saponins and gums. It exhibited antipyretic and analgesic activity at 200 and 400 mg/kg, while anti-inflammatory at 40, 80 and 160 Âµg/mL in the test systems. The activities were significant (p <0.05) in comparison to the negative control group with a high dose/concentration-mediated higher response manner. We suppose the alkaloids and glycosides may contribute its anti-inflammatory potential, which may link to the antipyretic and analgesic effects of the M. himalayana. In conclusion, M. himalayana may be one of the best sources of plant-based medicines, especially anti-inflammatory agents.